(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
This study was conducted to prepare and evaluate the quality and shelf life ofsmoked spotted snakehead, taki (Channapunctatus) stored at ambient temperature(30-35ºC) and refrigeration temperature (4ºC) after treating with no salt (T1) and 20%salt (T2). Sensory assessment, initial and final proximate analysis, TVB-N value andmicrobial analysis (SPC) were carried out for the smoked products stored for differentstorage periods. According to sensory assessment, smoked taki remained inacceptable condition for 4 and 6 days in T1 and T2, respectively while stored atambient temperature. However, at refrigeration temperature, smoked taki remained inacceptable condition for 59 and 74 days in T1 and T2, respectively. Biochemicalassessment of smoked product showed that protein, lipid and ash content increaseddue to significant loss of moisture during smoking of fish. No appreciable changes inproximate composition were observed for any of the two storage conditions. Valuesof TVB-N content of T1 showed rapid increase in comparison to T2 during storage.Microbial load (SPC) of smoked fish decreased due to the smoking processcompared to the initial microbial load of fresh fishes but increased with the increaseof storage period. Considering all the quality parameters it was found that smokedfish in treatment T2 maintained its excellent quality and longer shelf-life in bothstorage conditions than treatment T1. Res. Agric., Livest. Fish.7(2): 303-310, August 2020